The impact of crude oil prices, interest rates, and the Rupiah exchange rate on the transportation and logistics sector stock index (IDX-TRANS), 2021–2025 - Dias Febriansyah Subekti; Joy Elly Tulung; Priskila Bernita Rottie (Yayasan Widyantara Nawasena Raharja, 2026)
This study examines the impact of crude oil prices, interest rates, and the Rupiah exchange rate on the Transportation and Logistics Sector Stock Index (IDX-TRANS) on the Indonesia Stock Exchange for the period 2021–2025. Unlike prior sectoral studies that model a narrower set of macroeconomic drivers of IDX-TRANS, this study extends the specification by incorporating the BI Rate as an additional systematic risk factor and by explicitly controlling for the structural break associated with the COVID-19 mobility-restriction (PPKM) period. Grounded in Arbitrage Pricing Theory (APT) and the Efficient Market Hypothesis (EMH), this research employs a quantitative causal design using 59 monthly time-series observations (reduced from a nominal 60 months due to first-differencing). Variables are transformed into growth rates and first differences to satisfy stationarity requirements, confirmed using the Augmented Dickey-Fuller (ADF) test. Multiple linear regression analysis is conducted with inflation and a PPKM policy dummy as control variables, and classical assumption tests (normality, multicollinearity, autocorrelation, and heteroscedasticity) confirm that the model satisfies Best Linear Unbiased Estimator (BLUE) criteria. The simultaneous test (F-test) confirms that all variables jointly and significantly affect IDX-TRANS movements (Prob > F = 0.0062). Partially, interest rates (BI Rate) exert a significant negative effect (coefficient = −13.3604; p = 0.021), and the Rupiah exchange rate also has a significant negative effect (coefficient = −1.7850; p = 0.027), while crude oil prices show no significant effect (p = 0.547), attributed to the pass-through effect mechanism. The model explains 18.79% of IDX-TRANS variation (Adjusted R² = 0.1879). These findings suggest that monetary policy tightening and currency depreciation pose the greatest systemic risks to capital-intensive transportation firms in Indonesia.